Structural classification of vitamins P - A. Levitsky; V. Malinovskii (Journal of Education, Health and Sport)
It is proposed to classify the family of flavan-containing compounds depending on their chemical structure into 8 groups of vitamin P. Group I – flavanols, II – flavanones, III – flavones, IV – flavon-3-ols, V – anthocyanidins, VI – isoflavones, VII – chalcones, VIII – flavanlignans. Common properties for all groups of vitamin P are: increasing capillary resistance, antioxidant, anti-inflammatory and antimicrobial activity. It is necessary to study the dependence of biological and therapeutic and prophylactic properties of different groups of vitamin P on the features of the chemical structure.